T-cadherin, a major adiponectin binding partner, suppresses ERK signaling in metabolic tissues - Hirofumi Nagao; Yuta Kondo; Keitaro Kawada; Yuya Fujishima; Shunsuke Shiode; Yuhei Uehara; Shiro Fukuda; Yoshinari Obata; Shunbun Kita; Hitoshi Nishizawa; Iichiro Shimomura (Proceedings of the National Academy of Sciences, 2026)
T-cadherin, which is a major adiponectin binding partner, exerts various organ-protective effects. However, the specific changes in intracellular signaling that are induced by T-cadherin in metabolic tissues/cells remain unclear. We demonstrated that T-cadherin suppresses ERK signaling in both cultured cells and murine tissues. T-cadherin knockdown increased ERK phosphorylation in C2C12 myocytes and F2 endothelial cells, whereas T-cadherin overexpression suppressed ERK phosphorylation. Proteomic analysis revealed that many proteins that are downstream targets of ERK signaling were upregulated by T-cadherin knockdown in myocytes. T-cadherin knockdown in myocytes or knockout in heart or skeletal muscles altered the levels of membrane proteins that are involved in signal transduction, including IGF1R and EGFR. Ablation of T-cadherin in mice was accompanied by increased ERK signaling, leading to increased cardiac hypertrophy and decreased appropriate muscle atrophy during starvation. Thus, T-cadherin, whose protein expression is maintained by adiponectin, modulates intracellular signaling and regulates cardiac and skeletal muscle homeostasis in addition to promoting exosome production by adiponectin.